Anti‐Lingo‐1 antibody ameliorates spatial memory and synapse loss induced by chronic stress. Issue 7 (30th September 2020) - Xie, Yu‐han; Zhou, Chun‐ni; Liang, Xin; Tang, Jing; Yang, Chun‐mao; Luo, Yan‐min; Chao, Feng‐lei; Jiang, Lin; Wang, Jin; Qi, Ying‐qiang; Zhu, Pei‐lin; Li, Yue; et al.
Abstract: Chronic stress can induce cognitive impairment, and synapse number was significantly decreased in the hippocampus of rats suffering from chronic stress. Lingo‐1 is a potent negative regulator of axonal outgrowth and synaptic plasticity. In the current study, the effects of anti‐Lingo‐1 antibody on the spatial learning and memory abilities and hippocampal synapses of stressed rats were investigated. After 4 weeks of stress exposure, the model group was randomly divided into a chronic stress group and an anti‐Lingo‐1 group. Then, the anti‐Lingo‐1 group rats were treated with anti‐Lingo‐1 antibody (8 mg/kg) for 3 weeks. The effects of anti‐Lingo‐1 antibody on the spatial learning and memory abilities were investigated with the Morris water maze test. Immunohistological staining and an unbiased stereological method were used to estimate the total number of dendritic spine synapses in the hippocampus. At the behavioral level, after 3 weeks of treatment, the anti‐Lingo‐1 group rats displayed significantly more platform location crossings in the Morris water maze test than the chronic stress group rats. Anti‐Lingo‐1 significantly prevented the declines in dendritic spine synapses and postsynaptic density protein‐95 (PSD‐95) expression in the dentate gyrus and the CA1 and CA3 regions of the hippocampus. The present results indicated that anti‐Lingo‐1 antibody may be a safe and effective drug for alleviating memory impairment in rats after chronic stress and protecting synapses in the hippocampus of stressed rats. Highlights: Three weeks of anti‐Lingo‐1 antibody injection at a dose of 8 mg/(kg d) significantly improved the spatial memory ability of rats under chronic stress The synapses of the DG, CA1, and CA3 fields of the hippocampus were significantly decreased after 7 weeks of CS stimulation Three weeks of anti‐Lingo‐1 antibody treatment reversed the CS‐induced decrease in the synapses in the DG, CA1, and CA3 fields of the hippocampus